Lessons from past epidemics and pandemics and a way forward for pregnant women, midwives and nurses during COVID-19 and beyond: A meta-synthesis (2020)
Objective: To consolidate qualitative research studies that examined the experiences and needs of pregnant women, midwives, and nurses of maternity units to provide a way forward for future research and practices during the current pandemic and future epidemics and pandemics. Design: Qualitative systematic review and meta-synthesis. Data source: Four electronic databases—PubMed, Scopus, PsycINFO, and Cumulative Index to Nursing and Allied Health (CINAHL). Review methods: Qualitative studies with samples of pregnant women, midwives, and/or nurses of maternity units who experienced epidemics and/or pandemics were searched from 1 January 2000 to 4 April 2020. The included studies were critically appraised using the ten-item Critical Appraisal Skills Programme (CASP) tool. Findings: Eight studies were included in this review. Four themes emerged from the synthesis: (1) psychological responses, (2) challenges faced, (3) coping strategies, and (4) sources of support and support needs. Key conclusions: Pregnant women, midwives, and nurses experienced negative psychological responses during epidemics and pandemics. Challenges, such as limited available information and public stigma, were faced. Various coping strategies, such as actively looking for more information and seeking solace in religions, were practiced by pregnant women, midwives, and nurses. Families were both sources of support and stress and they expressed needs for more informational, emotional, and financial support during pandemics. Implications for practice: More culturally diverse research in the future that includes the development of technology-based programs, trained community volunteer-led programs, psychosocial interventions, and anti-stigma and awareness initiatives are needed to combat the current pandemic and future public health crises.